(untitled) (Global Journal of Science Frontier Research, 2023)
Through this article we offer you to highlight the important and vital role of microbial polymers by identifying them their types and their different uses in industry and agriculture and how to extract them from microbial environments in different ways The interest in this topic comes from the global concern based on preserving the environment and not using chemicals represented in pesticides and chemical fertilizers and their harmful effects on the environment climate changes and global warming and among them comes the interest in using natural materials produced by microbes which have a good effect on the environment and at the same time disposal Security from harmful pests using environmentally safe natural pesticides